Microalbuminuria and the Presence of Hypoxemia in Patients with Chronic Obstructive Pulmonary Disease - M. Rezwanuzzaman S.; K. Al Miraj A.; Majumder Shuvo; Hasan Zakir; Alam Kaoser; Uddin Patwary Nasir (Journal of Respiratory Diseases, 2022)
Introduction Worldwide, the Chronic Obstructive Pulmonary Disease (COPD) is a major public health concern; On the basis of epidemiologic data, by 2020, COPD will be the third leading cause of death worldwide. Objective To assess the frequency of Microalbuminuria and the presence of Hypoxemia in patients with COPD. Materials and Methods Study Design Cross-sectional observational study. Place of Study Department of Medicine & Respiratory Medicine in Dhaka Medical College Hospital (DMCH). Study Period Six months after approval of the protocol Study Population Patient suffering from COPD and admitted in Department of Medicine & Respiratory medicine, DMCH, Dhaka, Bangladesh. Total 100 samples were included in this study. COPD usually presents with a history of chronic cough with sputum production or exertional breathlessness which may be associated with relevant clinical findings and a post-bronchodilator FEV1/FVC less than 0.7. In most cases it is associated with smoking Results Total 100 patients of COPD were included in the study. Mean age was 58.16±5.4 years ranging from 50 to 74 years. Out of 100 patients, majority (42%) were from age group 55 to 60 years. Among all, 82% patients were male and 18% were female, of 100 patients, majority (30%) were day laborer. Only 2% were unemployed. The percentage of housewives was 18%. Other 34% were businessman and service holders. COPD severity was assessed using GOLD guideline. Out of 100 COPD patients, 38% had severe COPD (GOLD stage III). 16 % patients were in mild (Stage I) and 32% patients were in moderate stage (Stage II). The condition was very severe for 14% patients (Stage IV). Of 100 COPD patients, 30% had microalbuminuria. Among 100 COPD patients, chance of microalbuminuria increases among COPD patients with the increase of age significantly. There is smoking history of 36 pack year for COPD patients with microalbuminuria. Of 100 patients 26% were hypoxemic. The average forced expiratory volume (FEV1%) was 37.40 with standard deviation 14.48 for patients with microalbuminuria. The PaO2 and PaCO2 is 63.06 with standard deviation 7.09 and 46.09 with standard deviation 2.43 for COPD patients with microalbuminuria respectively. All of these characteristics are significant with p-value 0.00. However, the body mass index (BMI), systolic blood pressure (SBP) and diastolic blood pressure (DBP) were not found significant. The patients who had PaO2 less than 70 mmHg were considered hypoxemic. The patients who had microalbuminuria among them 87% were hypoxemic. Only 13% patients were free from hypoxemia who had microalbuminuria. Patients without microalbuminuria had no history of hypoxemia. There is significant relation exists between hypoxemia and the presence of microalbuminuria (p<0.5). Conclusion In this study, about one-fourth of the patients have hypoxemia and more than one fourth of the patients have microalbuminuria. Stage III was more frequent among the study population but there was no association between severity grading and presence of microalbuminuria. However, significant relation is found between co-existence of both microalbuminuria and hypoxemia in COPD patients.
Keywords: Microalbuminuria